ANALISIS REALISASI ANGGARAN DAN KINERJA PADA BADAN PERENCANAAN DAN PEMBANGUNAN DAERAH ( BAPPEDA ) PROPINSI KALIMANTAN BARAT - B51108016, JUNIO ARMANDA (Jurnal KIAFE, 2014)
This research is motivated that the budget was very influential in the organization of the government , both central and local government . Local budget and the budget is the main policy instrument for local governments as well as a tool used to evaluate or monitor the financial condition and operational implementation of programs or activities of the government . Therefore , the problem in this research is how the Budget and Actual Performance in BAPPEDA ordinance, while the purpose of this study was to determine the Actual Budget and Performan cehappens to BAPPEDA. The method used in this research is descriptive method through a case study with data collection by observation , interview and documentation studies . While the data used are secondary data derived from the performance reports for fiscal year 2011. Based on the research and analysis of the realization of the Budget Actual Budget and Performance on BAPPEDA Kalbar . It can be seen that the apparatus in BAPPEDA already perform tasks in creating and realizing maximum budget and performance in West Kalimantan . Although there are still some shortcomings because of constraints such as budget constraints owned , still less aware of the community to participate in a role in regional development , as well as the weakness of the human resources that still needs a lot of improvement of various sectors . Keywords : Performance , Budget , Realization